Of time and memory : a mother's story - Snyder, Don J (New York : Knopf : Distributed by Random House, 1999)
By retracing the steps of her youth, Snyder slowly unveils the love story between his mother and father -- as well as the stunning secret that made her death so unbearable
Keywords: Snyder, Don J. -- Family; Novelists, American -- 20th century -- Family relationships; Young women -- Pennsylvania -- Biography; Maternal deprivation -- Pennsylvania; Single-parent families -- Pennsylvania; Mothers -- Pennsylvania -- Biography; Mothers -- Pennsylvania -- Death; Authors, American -- Maine LOCATION